2021
DOI: 10.33393/jcb.2021.2212
|View full text |Cite
|
Sign up to set email alerts
|

Circulating progastrin-releasing peptide in the diagnosis of Small Cell Lung Cancer (SCLC) and in therapeutic monitoring

Abstract: Introduction: Progastrin-releasing peptide (proGRP), a precursor of GRP, has been recently reported as a putative circulating biomarker for differential diagnosis between non–small cell lung cancer (NSCLC) and SCLC. We evaluated the diagnostic effectiveness of proGRP to differentiate patients with NSCLC and SCLC and the usefulness of combined measurement of proGRP and neuron-specific enolase (NSE) for diagnosing SCLC. Methods: Serum proGRP, NSE, cytokeratin 19 fragment 21-1 (CYFRA 21.1), squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…An Italian study from 2021 [ 36 ] obtained similar results: higher levels of ProGRP were found in patients with SCLC (1484 pg/mL) compared to healthy subjects (36.1 pg/mL) and patients with non-SCLC (45 pg/mL).…”
Section: Discussionmentioning
confidence: 65%
“…An Italian study from 2021 [ 36 ] obtained similar results: higher levels of ProGRP were found in patients with SCLC (1484 pg/mL) compared to healthy subjects (36.1 pg/mL) and patients with non-SCLC (45 pg/mL).…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, especially ProGRP and NSE showed a good discriminative ability between NSCLC and SCLC, in accordance with our results. Barchiesi et al [26] conducted a small prospective investigation which validated the distinguishing capacity of NSE and, particularly, ProGRP (with a sensitivity of 82.4% and a specificity of 93.3%). This capability was further improved when both were used in combination (86.7% sensitivity at 96.6% specificity).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor markers are produced and secreted by human tumor tissues and cells [18] , and their levels are positively correlated with the severity of the patient's condition [19] NSE is a sensitive marker of neuroendocrine tumors, which can re ect the occurrence and progress of tumors; Pro GRP is an important marker for tumor condition and prognosis evaluation. Its expression level is positively correlated with the severity of the disease, which is of great signi cance for disease condition evaluation and prognosis prediction [20][21][22] . CYFRA21-1 can be released into the blood when tumor cells are lysed or necrotic, which has a high diagnostic and e cacy assessment in SCLC patients [23] .There was no signi cant difference between the two groups of patients before and after CEA treatment, which may be related to the fact that CEA positive rates are more frequently expressed in lung adenocarcinoma [24] .There was no signi cant difference in baseline markers between the two groups in this research.…”
Section: Discussionmentioning
confidence: 99%